Uncle Tom's cabin - Stowe, Harriet Beecher, 1811-1896 (Oxford world's classics (Oxford University Press), 1998)
Labeled racist and condescending by some contemporary critics, this novel remains a shocking, controversial, and powerful work that exposes the attitudes of white 19th century society toward the institution of slavery.